Positive electrode precursor material, preparation method thereof, positive electrode material and application
By step-by-step growth and control of the addition of crystal growth inducers, a loose core porous and dense external positive electrode precursor material is formed, which solves the nickel-lithium mixed displacement and phase transition problems of high-nickel positive electrode materials, and improves the safety, circulation performance and rate performance of the battery.
Patent Information
- Application Number
- CN202411767141.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-06
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
In the industrialization of existing high-nickel positive electrode materials, there are problems such as nickel-lithium mixed discharge, hindering Li+ diffusion, reducing discharge specific capacity and rate performance, and phase changes will occur during the charging and discharging process, affecting the thermal stability and cycling performance of the battery.
Through the step-by-step growth of precursor particles and the timing of adding crystal growth inducers is controlled, agglomeration between crystal nuclei is prevented, forming a loose, porous and radial arrangement of the core, and no crystal growth inducers are added to the second co-precipitation reaction to obtain external dense positive electrode precursor material.
The safety performance, circulation performance and rate performance of the cathode material are improved, the reaction with the electrolyte and gas production are reduced, and the deintercalation capability of Li+ is enhanced.
Smart Images

Figure CN119591174A_ABST
Abstract
Description
[0001] This application claims the priority of patent application No. 2024110708778 (the filing date of the prior application is August 6, 2024, and the name of the invention is A positive electrode precursor material and preparation method thereof, positive electrode material and application) Technical Field
[0002] The present invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode precursor material and a preparation method thereof, a positive electrode material and an application thereof. Background Art
[0003] With the reduction of non-renewable fossil energy and environmental problems, the development and utilization of new clean energy has received more and more attention. In the rapidly developing new energy vehicle industry, power lithium batteries are a key component. Lithium-ion batteries mainly include positive and negative electrode materials, diaphragms, electrolytes and current collectors, among which the performance of the positive electrode material will directly affect the battery's charge and discharge capacity, cycle performance, rate performance and high-temperature thermal stability.
[0004] As the requirements for energy density of power lithium batteries are getting higher and higher, high-nickel ternary materials with high specific capacity, low cost, and excellent safety are considered to be the most likely power battery positive electrode materials to be widely used. High-nickel materials have always been the focus of the new energy industry to solve the anxiety of battery life, but there are many problems in the industrialization of high-nickel materials, including the serious nickel-lithium mixing phenomenon with the increase of Ni content, which hinders the development of Li + Diffusion reduces the discharge capacity and rate performance, but high-nickel materials will undergo phase change, thermal stability and cycle performance reduction during the charging and discharging process, thus affecting the service life and safety of power lithium batteries for new energy vehicles. These technical barriers restrict the large-scale popularization of high-nickel materials.
[0005] To solve these technical problems, the safety and stability of the materials are often improved through bulk doping, outer layer coating and core-shell design.
[0006] CN106910874A discloses a method for simultaneously realizing surface coating and surface doping of high nickel materials, wherein after mixing a precursor with tetrabutyl titanate, a titanium dioxide coating layer is formed on the surface of the precursor by hydrolysis of tetrabutyl titanate, and a high nickel positive electrode material with surface Li2TiO3 coating and surface doping of Ti is formed in the subsequent mixed lithium-high temperature sintering process, and the synergistic effect of the two can effectively inhibit the interface reaction of the material, improve the structural stability and improve the electrochemical performance of the material. Although the synergistic effect of surface doping and coating can effectively improve the interface stability of the material, it often affects the conduction of electrons at the interface.
[0007] CN110429275A discloses a method for achieving carbon coating on the surface of a ternary positive electrode material in an organic liquid phase system using an organic carbon source in a low-temperature thermal reduction atmosphere, which improves the electronic conductivity of the material and enhances its cycle stability and rate performance. However, the increase in the coating material causes its discharge specific capacity at a small current to decrease. This is because the secondary sintering process in an argon atmosphere creates a micro-reducing environment, and the carbon captures the oxygen in the positive electrode material lattice, resulting in an increase in oxygen vacancies and lithium-nickel mixing, and a phase transition from layered to spinel phase to inert rock salt phase on the particle surface, which affects the deintercalation of lithium ions.
[0008] CN114408988A synthesizes a ternary positive electrode precursor by multi-step co-precipitation, which is divided into a rapid nucleation stage, a uniform growth stage and a slow growth stage. In the three stages, the reaction pH, ammonia concentration and reaction speed are constantly adjusted, and the flow rate of the oxidizing gas is also controlled to prepare a loose, porous precursor with a large specific surface area. The process control is relatively complex and the system is prone to fluctuations. In particular, when the oxidizing gas is introduced to control the oxidation of the material, the degree of oxidation is difficult to grasp, which is also prone to cause the problem of low production consistency.
[0009] The above-mentioned bulk doping, outer layer coating and core-shell design schemes have certain limitations for improving high-nickel materials.
[0010] Therefore, how to improve the safety, cycle performance and rate performance of positive electrode materials, especially high-nickel positive electrode materials, is a technical problem that needs to be solved urgently. Summary of the invention
[0011] In view of the shortcomings of the prior art, the object of the present invention is to provide a positive electrode precursor material and a preparation method thereof, a positive electrode material and application. The preparation method provided by the present invention prevents the agglomeration of the crystal nuclei of the precursor material by the step-by-step growth of the precursor particles and controls the timing of adding the crystal growth inducing agent, thereby ensuring the sphericity of the precursor, and obtaining a positive electrode precursor material with a loose and porous inner core, radial arrangement, and a relatively dense outer core, thereby improving the safety performance, cycle performance, and rate performance of the positive electrode material.
[0012] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0013] In a first aspect, the present invention provides a method for preparing a positive electrode precursor material, the preparation method comprising the following steps:
[0014] The first main metal element salt solution, the first precipitant solution and the first complexing agent solution are added to the bottom liquid in parallel to perform a first coprecipitation reaction. During the first coprecipitation reaction, a crystal growth inducing agent is added to obtain crystal nuclei;
[0015] After the first coprecipitation reaction is completed, a second main metal element salt solution, a second precipitant solution and a second complexing agent solution are added in parallel to continue the second coprecipitation reaction to obtain the positive electrode precursor material.
[0016] It should be noted that the types and concentrations of substances in the first main metal element salt solution and the second main metal element salt solution, the first precipitant solution and the second precipitant solution, the first complexing agent solution and the second complexing agent solution provided by the present invention may be the same or different; if they are different, then after the first coprecipitation reaction is completed, the addition of raw materials in the first coprecipitation reaction stage is stopped, and the addition of raw materials in the second coprecipitation reaction stage is carried out; if they are the same, the feed flow rate and reaction conditions of each raw material in the second coprecipitation reaction stage can be regulated; technical personnel in this field can select and regulate according to actual needs.
[0017] The preparation method provided by the present invention prevents agglomeration between crystal nuclei through step-by-step growth of precursor particles and controls the timing of adding a crystal growth inducer, thereby ensuring the sphericity of the precursor; in the first coprecipitation reaction process, a crystal growth inducer is added to make the crystal grow in a directional manner in the initial stage of crystal nucleation and growth, thereby forming a structure in which the primary particles of the inner core are radially arranged and the stacking is loose and porous and presents a divergent morphology; in the second coprecipitation reaction process, no crystal growth inducer is added, and the primary particles grown in this stage are thicker than the primary particles of the crystal nucleus in the first coprecipitation reaction, and the obtained external particles are relatively densely stacked, thereby reducing the reaction of the positive electrode with the electrolyte during the cycle, reducing gas production, and improving the safety and cycle performance of the material; and the inner core is loose and porous and radially arranged, so that the Li + Rapid embedding and de-embedding increases the rate performance of the material.
[0018] In the present invention, if a crystal growth inducer is not added and a staged preparation is simply performed, it is difficult to achieve controllable growth of crystals inside the particles, thereby failing to obtain a precursor morphology structure in which the inner cores are radially arranged; and if the addition sequence of the crystal growth inducer is adjusted, i.e., it is added in the second coprecipitation reaction stage, it will cause the seeds to aggregate more severely in the initial stage of nucleation and the sphericity to deteriorate, thereby affecting various indicators of the final product.
[0019] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0020] Preferably, the first main metal element includes nickel, and also includes any one of cobalt, manganese or aluminum, or a combination of at least two of them.
[0021] Preferably, the molar proportion of nickel in the first main metal element is 30-99%, for example 30%, 40%, 50%, 60%, 70%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] The preparation method provided by the present invention can solve the problems of various nickel contents, especially high-nickel materials (nickel molar ratio ≥ 80%); effectively suppress the lithium-nickel mixing phenomenon, and solve the phase change problem of high-nickel materials during the charging and discharging process; thereby improving the discharge capacity, rate performance, safety performance and cycle performance of high-nickel positive electrode materials.
[0023] Preferably, the concentration of the first main metal element salt solution is 1-4 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the concentration of the first precipitant solution is 1 to 3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the concentration of the first complexing agent solution is 1-3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the feed flow rate of the first main metal element salt solution is 15 to 30 kg / h, for example 15 kg / h, 18 kg / h, 20 kg / h, 24 kg / h, 25 kg / h, 28 kg / h or 30 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the feed flow rate of the first precipitant solution is 5 to 10 kg / h, for example 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h or 10 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the feed flow rate of the first complexing agent solution is 2-5 kg / h, such as 2 kg / h, 3 kg / h, 4 kg / h or 5 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the base solution comprises a solvent and a crystal growth inducing agent.
[0030] The present invention adds a crystal growth inducer to the base liquid, which is more conducive to the oriented growth of the precursor particles from the beginning of the reaction, ensures the sphericity of the particles, and also realizes radial arrangement of the primary particles inside the particles, presenting a loose and porous structure inside.
[0031] Preferably, the concentration of the crystal growth inducer in the base solution is 0.5-1 g / L, for example 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L or 1 g / L, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In the present invention, the concentration of the crystal growth inducer in the base solution is controlled to 0.5-1 g / L, which can better control the directional growth of crystals and form a loose and porous structure inside the particles.
[0033] Preferably, the crystal growth inducing agent comprises triethylamine.
[0034] Preferably, the crystal growth inducing agent is added intermittently during the first coprecipitation reaction.
[0035] In the present invention, the crystal growth inducer is intermittently added during the first coprecipitation reaction, which can improve the utilization rate of the crystal growth inducer and avoid the safety hazard caused by the high concentration of triethylamine in the reactor, and also avoid the possibility of the concentration of the crystal growth inducer decreasing with the increase of reaction time.
[0036] Preferably, during the first coprecipitation reaction, the crystal growth inducing agent is added every 4 hours.
[0037] Preferably, during the first coprecipitation reaction, the amount of the crystal growth inducer added each time is 0.1 to 0.5 kg, for example, 0.1 kg, 0.2 kg, 0.3 kg, 0.4 kg or 0.5 kg, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In the first coprecipitation reaction process, the present invention improves the ability of the crystal growth inducing agent to react and complex with the precipitant at the initial stage of the reaction through the coordinated coordination of the addition interval time and the dosage of the crystal growth inducing agent, thereby making the crystal show directional growth, ensuring the concentration content of the crystal growth inducing agent in the system, and making the operation simpler.
[0039] Preferably, the reaction temperature of the first coprecipitation reaction is 40-70°C, for example 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the pH value of the first coprecipitation reaction is 10-12, for example 10, 10.3, 10.5, 10.8, 11, 11.3, 11.5, 11.8 or 12, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the stirring speed of the first coprecipitation reaction is 200-380 r / min, for example, 200 r / min, 230 r / min, 250 r / min, 280 r / min, 300 r / min, 330 r / min, 350 r / min or 380 r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the average particle size of the crystal nucleus is 3 to 8 μm, for example 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] The average particle size of the crystal nuclei provided by the present invention is regulated to 3-8 μm, which, on the one hand, improves the sphericity of the obtained precursor material, and on the other hand, ensures the structural stability of the complete particles of the precursor material, so that the particle size is not too large to affect the sphericity of the final precursor, and is not too small to affect the growth rate of the second-stage precursor.
[0044] Preferably, the second main metal element includes nickel, and also includes any one of cobalt, manganese or aluminum, or a combination of at least two of them.
[0045] Preferably, the molar proportion of nickel in the second main metal element is 30-99%, for example 30%, 40%, 50%, 60%, 70%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, during the second co-precipitation process, a doping salt solution is also added in parallel.
[0047] In the second coprecipitation process of the present invention, doping elements are performed to further improve the electrochemical properties of the positive electrode material; and the type and amount of doping elements are selected according to conventional technology, and those skilled in the art can select and adjust them according to actual needs. The doping elements include but are not limited to zirconium, magnesium, ammonium or molybdenum.
[0048] Preferably, the concentration of the second main metal element salt solution is 1 to 4 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the concentration of the second precipitant solution is 1 to 3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the concentration of the second complexing agent solution is 1-3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the concentration of the doping salt solution is 1-4 mol / L, such as 1 mol / L, 2 mol / L, 3 mol / L or 4 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the feed flow rate of the first main metal element salt solution is 30-50 kg / h, for example, 30 kg / h, 33 kg / h, 35 kg / h, 38 kg / h, 40 kg / h, 43 kg / h, 45 kg / h, 48 kg / h or 50 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the feed flow rate of the first precipitant solution is 10 to 20 kg / h, for example 10 kg / h, 11 kg / h, 12 kg / h, 13 kg / h, 14 kg / h, 15 kg / h, 16 kg / h, 17 kg / h, 18 kg / h, 19 kg / h or 20 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the feed flow rate of the first complexing agent solution is 5-10 kg / h, for example 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h or 10 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the feed flow rate of the doping salt solution is 1 to 10 kg / h, for example, 1 kg / h, 2 kg / h, 3 kg / h, 4 kg / h, 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h or 10 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the reaction temperature of the second coprecipitation reaction is 40-70°C, for example 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the pH value of the second coprecipitation reaction is 9-11, for example 9, 9.3, 9.5, 9.8, 10, 10.3, 10.5, 10.8 or 11, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the stirring speed of the second coprecipitation reaction is 150-300 r / min, for example, 150 r / min, 180 r / min, 200 r / min, 230 r / min, 250 r / min, 280 r / min or 300 r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the average particle size of the positive electrode precursor material is 5 to 18 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] The preparation method provided by the present invention, under the action of a crystal growth inducer, regulates the concentration of raw materials, feed flow rate and reaction conditions in different reaction stages, thereby ensuring both the sphericity of the positive electrode precursor material particles and the stability of the structure, thereby subsequently obtaining a positive electrode material with a stable structure and excellent performance.
[0061] As a preferred technical solution, the preparation method comprises the following steps:
[0062] A first main metal element salt solution with a feed flow rate of 15 to 30 kg / h and a concentration of 1 to 4 mol / L, a first precipitant solution with a feed flow rate of 5 to 10 kg / h and a concentration of 1 to 3 mol / L, and a first complexing agent solution with a feed flow rate of 2 to 5 kg / h and a concentration of 1 to 3 mol / L are added to a base liquid in parallel, wherein the base liquid includes a crystal growth inducer with a concentration of 0.5 to 1 g / L, and a first coprecipitation reaction is carried out at 200 to 380 r / min and 40 to 70° C. in an environment with a pH value of 10 to 12. During the first coprecipitation reaction, the crystal growth inducer is added once every 4 hours, and the amount added each time is 0.1 to 0.5 kg, to obtain crystal nuclei with an average particle size of 3 to 8 μm;
[0063] After the first coprecipitation reaction is completed, a second main metal element salt solution with a feed flow rate of 30-50 kg / h and a concentration of 1-4 mol / L, a second precipitant solution with a feed flow rate of 10-20 kg / h and a concentration of 1-3 mol / L, a second complexing agent solution with a feed flow rate of 5-10 kg / h and a concentration of 1-3 mol / L, and a dopant solution with a feed flow rate of 1-10 kg / h and a concentration of 1-4 mol / L are added in parallel, and the second coprecipitation reaction is continued at 40-70° C. at 150-300 r / min in an environment of pH 9-11 to obtain a positive electrode precursor material with an average particle size of 5-18 μm.
[0064] It should also be noted that:
[0065] The material types of the first precipitant and the second precipitant in the present invention are selected by conventional technology, including but not limited to liquid alkali, such as sodium hydroxide or potassium hydroxide;
[0066] The material types of the first complexing agent and the second complexing agent in the present invention are selected according to conventional techniques, including but not limited to ammonia water, etc.;
[0067] The types of salts in the first main metal salt and the second main metal salt in the present invention are also selected according to conventional techniques, including but not limited to sulfates, chlorides or nitrates;
[0068] The base liquid of the present invention may also include a precipitant and a complexing agent; and the types and amounts of the precipitant and the complexing agent may be adaptively selected and adjusted.
[0069] In a second aspect, the present invention provides a positive electrode precursor material, which is prepared by the preparation method described in the first aspect; the positive electrode precursor material includes a core and an outer shell; the core is a porous structure; the density of the outer shell is higher than the density of the core.
[0070] The core in the present invention is the crystal core in the precursor material.
[0071] In a third aspect, the present invention provides a positive electrode material, which is obtained by mixing and sintering the positive electrode precursor material as described in the second aspect and a lithium source.
[0072] In the present invention, the method for preparing the positive electrode material from the positive electrode precursor material is a conventional technical means. Exemplarily, the present invention provides a preparation process of the positive electrode material:
[0073] The cathode precursor material of the second aspect and the lithium source are uniformly mixed at a molar ratio of Me:Li of 1:(1-1.5), sintered at a sintering temperature of 500-1000 for 6-20h in an oxygen-containing atmosphere, and cooled naturally to room temperature to obtain a cathode material;
[0074] Optionally, the lithium source includes but is not limited to at least one of lithium hydroxide, lithium carbonate or lithium acetate; the oxygen-containing atmosphere includes air atmosphere or oxygen atmosphere, etc.
[0075] Those skilled in the art can make adaptive selection and adjustment of the above preparation process and parameters according to actual needs.
[0076] In a fourth aspect, the present invention further provides a battery, comprising the positive electrode material as described in the third aspect.
[0077] Compared with the prior art, the present invention has the following beneficial effects:
[0078] The preparation method provided by the present invention prevents agglomeration between crystal nuclei and ensures the sphericity of the precursor by controlling the step-by-step growth of precursor particles and the timing of adding a crystal growth inducer; in the first coprecipitation reaction process, a crystal growth inducer is added to make the crystal grow in a directional manner in the early stages of crystal nucleation and growth, forming a structure in which the primary particles of the inner core are radially arranged and the stacking is loose and porous and presents a divergent morphology; in the second coprecipitation reaction process, no crystal growth inducer is added, and the primary particles grown in this stage are coarser and thicker than the primary particles of the crystal nucleus in the first coprecipitation reaction, and the obtained external particles are relatively densely stacked, so that the positive electrode reduces the reaction with the electrolyte during the cycle process, reduces gas production, and improves the safety and cycle performance of the material; and the inner core is loose and porous and arranged radially, so that Li+ is quickly deintercalated during the cycle process, thereby increasing the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is the SEM image of the positive electrode precursor material provided in Example 1.
[0080] Figure 2 This is a SEM image of the cross-section of the positive electrode precursor material provided in Example 1. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0083] In the description of this application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0084] Example 1
[0085] This embodiment provides a method for preparing a positive electrode precursor material, and the preparation method is as follows:
[0086] (1) nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 0.98:0.01:0.01 to prepare a nickel-cobalt-manganese metal salt solution A with a total metal ion concentration of 2 mol / L, and an ammonia complexing agent solution with a concentration of 1 mol / L; and OH - A 2 mol / L liquid alkali solution (sodium hydroxide); a 2 mol / L zirconium sulfate solution (doped salt solution);
[0087] (2) Add 400 L of pure water, ammonia water, alkaline solution and 0.5 kg of crystal growth inducer triethylamine as the bottom liquid to a 1000 L reactor to maintain the stability of the system;
[0088] The mixed solution A, the ammonia complexing agent, and the liquid alkali solution were added to the reactor at flow rates of 15 kg / h, 5 kg / h, and 2 kg / h, respectively, and the first coprecipitation reaction was carried out at 40°C. 200 g (0.2 kg) of triethylamine was added every 4 hours to maintain the reaction pH at 10.5, the ammonia concentration at 11 g / L, and the stirring speed at 300 r / min; when the average particle size of the precursor reached 6 μm, the first coprecipitation reaction was stopped to obtain crystal nuclei;
[0089] (3) Changing the feed flow rate, the mixed solution A, the ammonia complexing agent, the precipitant solution and the zirconium sulfate solution were continuously added to the reactor at flow rates of 30 kg / h, 10 kg / h, 5 kg / h and 1.5 kg / h, respectively, and a second coprecipitation reaction was carried out at 50° C. (without adding a crystal growth inducing agent), the reaction pH was maintained at 9.8, the ammonia concentration was 9 g / L, the stirring speed was 200 r / min, and the reaction was stopped after the average particle size of the particles reached 15 μm. After filtering, washing and drying, a spherical precursor Ni with an average particle size of 15 μm was obtained. 0.97 Co 0.01 Mn 0.01 Zr 0.01 (OH)2, the inner core (i.e., crystal nucleus) is divergent and loosely stacked, while the outer part is a densely stacked structure.
[0090] Figure 1 The SEM image of the positive electrode precursor material provided in Example 1 is shown. Figure 1 It can be seen that the positive electrode precursor material obtained by the preparation method provided by the present invention has high sphericity and uniform particle size.
[0091] Figure 2 The SEM image of the cross section of the positive electrode precursor material provided in Example 1 is shown. Figure 2 It can be seen that the positive electrode precursor material prepared by the present invention has radially arranged internal grains, is loose and porous, and has a denser external structure.
[0092] Example 2
[0093] This embodiment provides a method for preparing a positive electrode precursor material, and the preparation method is as follows:
[0094] (1) nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 0.88:0.05:0.07 to prepare a nickel-cobalt-manganese metal salt solution A with a total metal ion concentration of 3 mol / L, and an ammonia complexing agent solution with a concentration of 2 mol / L; OH - A 2 mol / L liquid alkali solution (sodium hydroxide); a 2 mol / L zirconium sulfate solution (doped salt solution);
[0095] (2) Add 400 L of pure water, ammonia water, alkaline solution and 0.8 kg of crystal growth inducer triethylamine as the bottom liquid to a 1000 L reactor to maintain the stability of the system;
[0096] The mixed solution A, the ammonia complexing agent, and the liquid alkali solution were added to the reactor at flow rates of 20 kg / h, 7.5 kg / h, and 3 kg / h, respectively, and the first coprecipitation reaction was carried out at 45°C. 300 g of triethylamine was added every 4 hours to maintain the reaction pH at 11.8, the ammonia concentration at 9 g / L, and the stirring speed at 350 r / min. When the average particle size of the precursor reached 4 μm, the first coprecipitation reaction was stopped to obtain crystal nuclei;
[0097] (3) Changing the feed flow rate, the mixed solution A, the ammonia complexing agent, the precipitant solution and the magnesium sulfate solution were continuously added to the reactor at flow rates of 40 kg / h, 15 kg / h, 7 kg / h and 5 kg / h, respectively, and a second coprecipitation reaction was carried out at 50° C. (without adding a crystal growth inducing agent), the reaction pH was maintained at 10.5, the ammonia concentration was 7 g / L, the stirring speed was 280 r / min, and the reaction was stopped after the average particle size of the particles reached 10 μm. After filtering, washing and drying, a spherical precursor Ni with an average particle size of 10 μm was obtained. 0.87 Co 0.04 Mn 0.06 Mg 0.03 (OH)2, the inner core (i.e., crystal nucleus) is divergent and loosely stacked, while the outer part is a densely stacked structure.
[0098] Example 3
[0099] This embodiment provides a method for preparing a positive electrode precursor material, and the preparation method is as follows:
[0100] (1) nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 0.98:0.01:0.01 to prepare a nickel-cobalt-manganese metal salt solution A with a total metal ion concentration of 1 mol / L, and an ammonia complexing agent solution with a concentration of 1 mol / L; and OH - A 1 mol / L liquid alkali solution (sodium hydroxide); a 1 mol / L zirconium sulfate solution (doped salt solution);
[0101] (2) Add 400 L of pure water, ammonia water, alkaline solution and 1 kg of crystal growth inducer triethylamine as the bottom liquid to a 1000 L reactor to maintain the stability of the system;
[0102] The mixed solution A, the ammonia complexing agent and the liquid alkali solution were added to the reactor at a flow rate of 30 kg / h, 10 kg / h and 5 kg / h respectively, and the first coprecipitation reaction was carried out at 55°C. 500 g of triethylamine was added every 4 hours to maintain the reaction pH at 10.5, the ammonia concentration at 10 g / L, and the stirring speed at 250 r / min; when the average particle size of the precursor reached 3 μm, the first coprecipitation reaction was stopped to obtain crystal nuclei;
[0103] (3) Changing the feed flow rate, the mixed solution A, the ammonia complexing agent, the precipitant solution and the zirconium sulfate solution were continuously added to the reactor at flow rates of 50 kg / h, 20 kg / h, 10 kg / h and 10 kg / h, respectively, and a second coprecipitation reaction was carried out at 55° C. (without adding a crystal growth inducer), the reaction pH was maintained at 9.8, the ammonia concentration was 8 g / L, the stirring speed was 150 r / min, and the reaction was stopped after the average particle size of the particles reached 5 μm. After filtering, washing and drying, a spherical precursor Ni with an average particle size of 15 μm was obtained. 0.97 Co 0.01 Mn 0.01 Zr 0.01 (OH)2, the inner core (i.e., crystal nucleus) is divergent and loosely stacked, while the outer part is a densely stacked structure.
[0104] Example 4
[0105] The difference between this embodiment and embodiment 1 is that in this embodiment, no crystal growth inducing agent is added to the base solution in step (2).
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 5
[0108] The difference between this embodiment and embodiment 1 is that in the base liquid of step (2) of this embodiment, the amount of crystal growth inducer added is 1.5 kg.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 6
[0111] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, during the first stage of the coprecipitation reaction, a crystal growth inducing agent is continuously added, and the feed flow rate is 50 g / h.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 7
[0114] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, during the first coprecipitation reaction, 200 g of crystal growth inducer is added every 10 hours.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 8
[0117] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, during the first coprecipitation reaction, no crystal growth inducing agent is added except to the base liquid.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Example 9
[0120] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, during the first coprecipitation reaction, 50 g of a crystal growth inducer is added every 4 hours.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Example 10
[0123] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, during the first coprecipitation reaction, 1 kg of crystal growth inducer is added every 4 hours.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Embodiment 11
[0126] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, during the second coprecipitation reaction, the feed flow rates of the mixed solution A, the ammonia complexing agent solution and the precipitant solution remain consistent with the feed flow rates during the first coprecipitation reaction.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, no crystal growth inducing agent is added to the base liquid and in the first coprecipitation reaction stage.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the crystal growth inducer is added in the second coprecipitation reaction stage, and 30 mL of the crystal growth inducer is still added every 5 hours, and the base liquid does not contain the crystal growth inducer.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] [Preparation of positive electrode materials]
[0135] The positive electrode precursor materials provided in Example 1-11 and Comparative Example 1-2 were calcined with lithium hydroxide respectively, the ratio of the precursor to the lithium source was 1:1.5, and they were mixed evenly by a high-speed mixer. They were sintered in a box furnace under an air atmosphere at a sintering temperature of 800°C and a high-temperature sintering time of 12 hours. After cooling to room temperature, they were crushed and sieved to obtain the positive electrode material.
[0136] [Preparation and performance testing of lithium-ion batteries]
[0137] Preparation of lithium-ion batteries:
[0138] The positive electrode materials, conductive carbon black SP (TIMCAL), and polyvinylidene fluoride PVDF (HSV900) provided in Examples 1-11 and Comparative Examples 1-2 were mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone was used as a solvent to mix and stir into a slurry. The obtained slurry was evenly coated on an aluminum foil with a scraper with a coating gap of 100 μm. After coating, it was first dried at 120°C by blast drying, then rolled, and finally the dried electrode sheet was cut into Φ12 circular electrode sheets. After vacuum drying at 120°C, the electrode sheet was weighed to obtain a button half-cell positive electrode sheet; the negative electrode selected a Φ14 metal lithium sheet, the diaphragm was a Φ19 PP microporous membrane (Celgard2400), and the electrolyte selected a lithium battery basic electrolyte, that is, EC and DEC were used as a mixed solvent in a volume ratio of 1:1, 1.1 mol / L LiPF6 was added, and the positive electrode sheet, metal lithium sheet, diaphragm and electrolyte were assembled to obtain a button cell.
[0139] Button cell performance test: the capacity was tested at 0.1C for charge and discharge, and at 1C for charge and discharge cycles. The test results are shown in Table 1.
[0140] Table 1
[0141]
[0142]
[0143] From Table 1, we can get:
[0144] It can be seen from the data results of Example 1 and Example 4 that not adding a crystal growth inducer to the base solution is not conducive to the formation of a loose and porous structure inside the precursor particles, thereby resulting in a decrease in both capacity and cycle performance.
[0145] It can be seen from the data results of Example 1 and Example 5 that adding too much crystal growth inducer to the base liquid will also affect the structural stability of the material, thereby causing performance degradation.
[0146] It can be seen from the data results of Example 1 and Example 6 that during the first coprecipitation reaction, the continuous addition of the crystal growth inducing agent cannot ensure the stability of the concentration of the crystal growth inducing agent in the system, thereby affecting the electrochemical performance.
[0147] From the data results of Example 1 and Examples 7-10, it can be seen that by regulating the addition time and amount of the crystal growth inducer in addition to the base liquid during the first co-precipitation reaction, the ability of the crystal growth inducer to react and complex with the precipitant in the early stage of the reaction can be further improved, thereby making the crystal grow in a directional manner, ensuring the concentration of the crystal growth inducer in the system, and thereby improving the electrochemical performance of the battery.
[0148] It can be seen from the data results of Example 1 and Example 11 that by regulating the feed flow rate of raw materials in different reaction stages, the sphericity of the positive electrode precursor material particles and the stability of the structure are guaranteed, so that a positive electrode material with stable structure and excellent performance can be obtained subsequently.
[0149] It can be seen from the data results of Example 1 and Comparative Examples 1 and 2 that without adding a crystal growth inducer, it is difficult to achieve a structure of a precursor material that is loose and porous inside and relatively dense outside, thereby failing to improve the safety performance, cycle performance and rate performance of the positive electrode material; and if the timing of adding the crystal growth inducer is adjusted, the outside of the positive electrode precursor will become looser, failing to solve the gas production problem of the positive electrode material.
[0150] In summary, the preparation method provided by the present invention prevents agglomeration between crystal nuclei and ensures the sphericity of the precursor by the step-by-step growth of precursor particles and controlling the timing of adding a crystal growth inducer; adds a crystal growth inducer during the first coprecipitation reaction to allow the crystal to grow in a directional manner during the initial stage of crystal nucleation and growth, thereby forming a structure in which the primary particles of the inner core are radially arranged and the stacking is loose, porous and divergent in morphology; does not add a crystal growth inducer during the second coprecipitation reaction, and the primary particles grown in this stage are coarser and thicker than the primary particles of the crystal nucleus in the first coprecipitation reaction, and the obtained external particles are relatively densely stacked, thereby reducing the reaction of the positive electrode with the electrolyte during the cycle, reducing gas production, and improving the safety and cycle performance of the material; and the inner core is loose and porous and radially arranged, so that Li+ is quickly deintercalated during the cycle, thereby increasing the rate performance of the material.
[0151] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a positive electrode precursor material, characterized in that: The preparation method comprises the following steps: The first main metal element salt solution, the first precipitant solution and the first complexing agent solution are added to the bottom liquid in parallel to perform a first coprecipitation reaction. During the first coprecipitation reaction, a crystal growth inducing agent is added to obtain crystal nuclei; After the first coprecipitation reaction is completed, a second main metal element salt solution, a second precipitant solution and a second complexing agent solution are added in parallel to continue the second coprecipitation reaction to obtain the positive electrode precursor material.
2. The preparation method according to claim 1, characterized in that: The first main metal element includes nickel, and also includes any one or a combination of at least two of cobalt, manganese or aluminum; Preferably, the molar proportion of nickel in the first main metal element is 30-99%; Preferably, the concentration of the first main metal element salt solution is 1 to 4 mol / L; Preferably, the concentration of the first precipitant solution is 1 to 3 mol / L; Preferably, the concentration of the first complexing agent solution is 1 to 3 mol / L; Preferably, the feed flow rate of the first main metal element salt solution is 15-30 kg / h; Preferably, the feed flow rate of the first precipitant solution is 5 to 10 kg / h; Preferably, the feed flow rate of the first complexing agent solution is 2-5 kg / h.
3. The preparation method according to claim 1 or 2, characterized in that: The base liquid includes a solvent and a crystal growth inducing agent; Preferably, the concentration of the crystal growth inducing agent in the base solution is 0.5 to 1 g / L; Preferably, the crystal growth inducing agent comprises triethylamine; Preferably, the crystal growth inducing agent is added intermittently during the first coprecipitation reaction; Preferably, during the first coprecipitation reaction, the crystal growth inducing agent is added every 4 hours; Preferably, during the first coprecipitation reaction, the amount of the crystal growth inducer added each time is 0.1 to 0.5 kg.
4. The preparation method according to any one of claims 1 to 3, characterized in that The reaction temperature of the first coprecipitation reaction is 40 to 70° C. Preferably, the pH value of the first coprecipitation reaction is 10 to 12; Preferably, the stirring speed of the first coprecipitation reaction is 200 to 380 r / min; Preferably, the average particle size of the crystal nuclei is 3 to 8 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The second main metal element includes nickel, and also includes any one or a combination of at least two of cobalt, manganese or aluminum; Preferably, the molar proportion of nickel in the second main metal element is 30-99%; Preferably, during the second co-precipitation process, a doping salt solution is also added in parallel; Preferably, the concentration of the second main metal element salt solution is 1 to 4 mol / L; Preferably, the concentration of the second precipitant solution is 1 to 3 mol / L; Preferably, the concentration of the second complexing agent solution is 1 to 3 mol / L; Preferably, the concentration of the doping salt solution is 1 to 4 mol / L; Preferably, the feed flow rate of the first main metal element salt solution is 30-50 kg / h; Preferably, the feed flow rate of the first precipitant solution is 10 to 20 kg / h; Preferably, the feed flow rate of the first complexing agent solution is 5 to 10 kg / h; Preferably, the feed flow rate of the doping salt solution is 1-10 kg / h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The reaction temperature of the second coprecipitation reaction is 40 to 70° C.; Preferably, the pH value of the second coprecipitation reaction is 9 to 11; Preferably, the stirring speed of the second coprecipitation reaction is 150 to 300 r / min; Preferably, the average particle size of the positive electrode precursor material is 5 to 18 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: A first main metal element salt solution with a feed flow rate of 15 to 30 kg / h and a concentration of 1 to 4 mol / L, a first precipitant solution with a feed flow rate of 5 to 10 kg / h and a concentration of 1 to 3 mol / L, and a first complexing agent solution with a feed flow rate of 2 to 5 kg / h and a concentration of 1 to 3 mol / L are added to a base liquid in parallel, wherein the base liquid includes a crystal growth inducer with a concentration of 0.5 to 1 g / L, and a first coprecipitation reaction is carried out at 200 to 380 r / min and 40 to 70° C. in an environment with a pH value of 10 to 12. During the first coprecipitation reaction, the crystal growth inducer is added once every 4 hours, and the amount added each time is 0.1 to 0.5 kg, to obtain crystal nuclei with an average particle size of 3 to 8 μm; After the first coprecipitation reaction is completed, a second main metal element salt solution with a feed flow rate of 30-50 kg / h and a concentration of 1-4 mol / L, a second precipitant solution with a feed flow rate of 10-20 kg / h and a concentration of 1-3 mol / L, a second complexing agent solution with a feed flow rate of 5-10 kg / h and a concentration of 1-3 mol / L, and a dopant solution with a feed flow rate of 1-10 kg / h and a concentration of 1-4 mol / L are added in parallel, and the second coprecipitation reaction is continued at 40-70° C. at 150-300 r / min in an environment of pH 9-11 to obtain a positive electrode precursor material with an average particle size of 5-18 μm.
8. A positive electrode precursor material, characterized in that: The positive electrode precursor material is prepared by the preparation method according to any one of claims 1 to 7; the positive electrode precursor material comprises a core and an outer shell; the core is a porous structure; the density of the outer shell is higher than the density of the core.
9. A positive electrode material, characterized in that: The positive electrode material is obtained by mixing and sintering the positive electrode precursor material as claimed in claim 8 and a lithium source.
10. A battery, characterized in that: The battery comprises the positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
High-nickel material coated with Li2TiO3 on surface and doped with Ti on surface layer and preparation method
CN106910874A
A preparation method of a carbon-coated ternary positive electrode material and the carbon-coated ternary positive electrode material
CN110429275A
Ternary positive electrode material precursor and preparation method thereof
CN114408988A
Cited By
Positive electrode precursor material and preparation method therefor, and positive electrode material and use thereof
WO2026031574A1